Lithium use during breastfeeding was safe in healthy full‐term infants under strict monitoring. (17th June 2022) - Heinonen, Essi; Tötterman, Katarina; Bäck, Karin; Sarman, Ihsan; Svedenkrans, Jenny; Forsberg, Lisa
Abstract: Aim: Previous studies on breastfeeding during lithium therapy have shown conflicting results. The aim of this study was to evaluate the safety when practising thorough follow‐up of the infants. Method: This retrospective study focused on women with lithium medication, and their breastfed infants born between 2006 and 2021 in Stockholm, Sweden. Information about infant serum lithium concentrations and clinical status was collected from medical records. Results: In total, 30 infants exposed to lithium through breastmilk, 21 girls and 9 boys, were included. The median age at follow‐up was 40 days (range 8–364 days). The median lithium serum concentration was 0.10 mmol/L in the second week of life (range <0.05–0.7 mmol/L), 0.08 in week 2–4 (range <0.05–1.2), 0.06 in the second month of life (range <0.05–0.2) and 0.07 after 2 months of age (range <0.05–0.2). Unexpectedly high lithium concentrations were found in two infants in the first month of life. Apart from poor weight gain, no adverse effects were found. Conclusion: Serum lithium concentrations in breastfed infants were stabilised at barely measurable levels after the first weeks of life. Before that, concentrations higher than the mothers were found. Lithium treatment during breastfeeding can be considered safe under strict follow‐up.